Проблема свободи волі: історико-філософські сюжети в аналітичній перспективі. Hausmannn, M., & Noller, J. (Eds.). (2021). Free Will. Historical and Analytic Perspectives. Cham: Springer; London: Palgrave Macmillan. - Сепетий, Дмитро Петрович; Sepetyi, D. (My University, 2022)
Огляд книги Hausmannn, M., & Noller, J. (Eds.). (2021). Free Will. Historical and Analytic Perspectives. Cham: Springer; Palgrave Macmillan. Rewiew of Hausmannn, M., & Noller, J. (Eds.). (2021). Free Will. Historical and Analytic Perspectives. Cham: Springer; Palgrave Macmillan.
The problem of the freedom of will: historico-philosophical topics in the analytic perspective. Hausmannn, M., & Noller, J. (Eds.). (2021). Free Will. Historical and Analytic Perspectives. Cham: Springer; London: Palgrave Macmillan.